The development of the collision of the right to the protection of personal data and the freedom of expression under EU data protection law: analysis of the relevant case law of the CJEU and Latvia’s approach on the reconciliation of the national rules governing freedom of expression and information, including journalistic, academic, artistic and or literary expression with the right to the protection of personal data pursuant to Article 85 of GDPR - Mauriņa, Liene (Riga Graduate School of Law, 2019)
This master thesis explores the historical development of the EU’s legal framework aiming to reconcile the right to the protection of personal data and the right to freedom of expression and information. In particularly, this master thesis provides a review of the two main EU secondary law sources forming the previous and the existing EU’s personal data protection framework - the Data Protection Directive and GDPR in the light of the relevant case law of the CJEU dealing with interpretation of the special purposes exception provided under the Data Protection Directive. Even more, this master thesis aims to determine, whether the specific rules provided under Article 85 of GDPR corresponds to the particular jurisprudence of the CJEU, as well as studies if the approach taken by the Latvian legislator under Article 85 of GDPR is consistent with the rulings of the CJEU as well as reflects and effectively reach the goal of coherent reconciliation between the right to the protection of personal data and the freedom of expression and information pursuant to Article 85 of GDPR among the Member States.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Data protection